The changing urban landscape of Chinese cities: positive and negative impacts of urban design controls on contemporary urban housing - Cheshmehzangi, Ali (MDPI, 2018)
China’s contemporary urban housing is increasingly developed at mass housing scale. In recent decades, it has transformed into large scale urban design approach rather than individual architectural design. This is generally common across major Chinese cities and is also becoming the case in some township regions. The increase in mass urban housing production firstly initiated in early years after establishment of the People’s Republic of China in 1949 and was then increased significantly from the 1970s onwards. Similar to the case of post-war European housing development in the 1950s and 1960s, China experienced a rapid transition and huge demand for new urban housing. The two decades of 1980s and 1990s are known as China’s remarkable era for rapid growth and urbanisation, which was unprecedented not only for China but also globally. In this paper, the focus is on urban design controls and their impacts on housing transitions in China by first analysing common housing typologies as well as their challenges and issues and common practices of urban design for housing projects across major cities of China. This paper argues in favour of alternative routes before concluding on the importance of detailed design and new possibilities for revised and re-evaluated urban design controls. This paper offers a set of analytical views on positive and negative impacts of urban design controls on contemporary urban housing in China. It also adds to existing research focused on urban housing transitions in China and directly linked to sectors of urban planning and urban design. This study concludes with possibilities for new directions, focused on: development of low- to midrise urban housing typology, compact urban development, and avoidance of gated community development.